2018
DOI: 10.1007/s11356-018-1761-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biotoxicity of Cu nanoparticles with respect to probiotic strains of microorganisms and representatives of the normal flora of the intestine of broiler chickens

Abstract: Copper nanoparticle Cu (d = 55 ± 15 nm) and CuO nanoparticles (d = 90 ± 10 nm) were used in the studies (OOO Platina, Russia). Using the method of pure cultures, we extracted Lactobacillus, Enterococcus, and Enterobacterium from the intestines of broilers. Additionally, strains of Bacillus subtilis 10641 and Bifidobacterium were involved in probiotic strains. The data obtained in the course of the study testify to the insignificant biotoxicity of copper nanoparticles with respect to representatives of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In groups I and II, representatives of class Clostridia decreased by 14.6-50.5% in comparison with the control. Earlier studies also demonstrated the positive effect of tannincontaining substances on inhibition of the development of microorganisms of class Clostridia [13], as well as the great variability in the development of micro-organisms in the small intestine of broilers [14]. Speaking of the cecal intestine, we recorded an increase of phylum Firmicutes due to representatives of classes Clostridia and Bacillus and the absence of representatives of phylum Bacteroidetes in the second group.…”
Section: Resultssupporting
confidence: 71%
“…In groups I and II, representatives of class Clostridia decreased by 14.6-50.5% in comparison with the control. Earlier studies also demonstrated the positive effect of tannincontaining substances on inhibition of the development of microorganisms of class Clostridia [13], as well as the great variability in the development of micro-organisms in the small intestine of broilers [14]. Speaking of the cecal intestine, we recorded an increase of phylum Firmicutes due to representatives of classes Clostridia and Bacillus and the absence of representatives of phylum Bacteroidetes in the second group.…”
Section: Resultssupporting
confidence: 71%
“…In another study, in poultry, CuO NP added to the feed, did not affect probiotics or the main representatives of normal microbial community. The Cu active ions, due to the low dissociation degree from NP, are released more slowly and therefore have more prolonged positive effects (94).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…It is also used as a probiotic to promote the growth of broiler chicken or shrimp. Several studies have shown that the co-administration of nanoparticles and probiotics has no or few effect on the microbiome composition or activity [49,50]. But chronic oral absorption of nanoparticles, as a consequence of nanoparticles in food additives, disturbs the gut microbiome equilibrium and may be responsible for several chronic diseases [51].…”
Section: Plos Onementioning
confidence: 99%